The inflammatory profile of chronic kidney disease patients - Chaker, Hanen; Jarraya, Faiçal; Toumi, Salma; Kammoun, Khawla; Mahfoudh, Hichem; Ayadi, Fatma; Yaich, Soumaya; Hmida, Mohamed Ben (Journal of Clinical Nephrology, 2021)
Background: Chronic kidney disease is a worldwide public health issue which is associated with an increased risk of end-stage renal failure and cardiovascular disease. Systemic inflammation exists during chronic renal failure. Recent researches have highlighted the pivotal role of inflammation between renal and cardiovascular disease. The aim of our study is to determine the inflammatory profile of the patient suffering from chronic kidney disease and the influence of hemodialysis on this profile. Methods: We carried out a cross sectional study on 93 patients in the Nephrology Department at Hedi Chaker University Hospital, Sfax, South of Tunisia. Among those patients, 72 patients underwent hemodialysis and 21 patients had chronic kidney disease at stage 3. Clinical data and antecedents were collected. Biological samples were taken after informing the patients and taking their consent. Biological data consisted in lipid profile, albumin rate, hemoglobin rate, uric acid concentration and the usual markers of inflammation noting sedimentation rate, C - reactive protein and orosomucoid. Results: Hemodialysis group of the 72 patients had mean hemodialysis vintage of 54.6 ± 43 months. The inflammatory profile was worse in hemodialysis patients compared to chronic kidney disease patients. Both sedimentation rate, C - reactive protein and orosomucoid were higher in hemodialysis group than in chronic kidney disease group with 71 ± 35.3 mm vs. 42.1 ± 15.5 mm (p < 0.05); 14.6 ± 28.7 mg/l vs. 6.7 ± 8 mg/l (p = 0.02); 1.3 ± 0.7g/l vs. 0.9 ± 0.4 g/l (p = 0.01), respectively. Conclusion: Inflammation increases in dialysis patient. It deserves the nephrologist’s consideration in order to minimize its harmful effects. The monitoring of inflammation markers must be integrated into the nephrologist’s medical practice.